Institutions complement diffusion but reconfigure enablers on the road to triple transition: evidence from Creative Europe projects - Turegeldinova, Aliya; Amralinova, Bakytzhan; Fodor, Máté Miklós; Eraliyeva, Akerkin; Dayou, Chen; Joldassov, Aidos (Frontiers in Communication, 2025)
IntroductionEuropean policy promotes a “triple transition” integrating digital innovation, ecological sustainability, and social inclusion. Creative industries are well positioned to contribute given their societal role beyond production and their capacity to shape responses to shared challenges. This study examines how a policy mandate interacts with organic innovation dynamics in achieving simultaneous integration of all three pillars in publicly funded projects.MethodsWe analyze 5,601 initiatives supported by the European Union’s Creative Europe program (2013 -2025). Beginning in 2021, calls for proposals encouraged inclusion of all three pillars, creating a policy shift we use as a natural experiment to compare pre_ and post_2021 patterns. We identify “triple_pillar” projects, i.e. those explicitly targeting digital, green, and social aims and examine the predictors of their prevalence, including partnership scope (single_ vs. multi_country) and financial scale (project budgets and grant amounts).ResultsThe share of triple_pillar projects rose steadily even before 2021 and continued increasing afterward. However, the mandate substituted for other catalysts like international collaboration. Pre-2021, multi-country partnerships significantly predicted triple-focus within projects. Post-2021 however, this link vanished as even local projects complied with Creative Europe’s suggestions. Instead, larger project budgets and grants emerged as key enablers, indicating a trade-off in cost efficiency. Mandated comprehensiveness required greater resources for implementation.DiscussionPolicy cues can amplify initiatives already emerging from project participants, but they also reshape implementation. In this analytical framework, away from international collaboration as a catalyst and toward financing capacity. This could potentially disadvantage smaller actors. To maximize impact and cost efficiency, mandates should be paired with proportionate funding and flexible pathways.